Use of Scrap Tyre as Lightweight Material In Civil Engineering Infrastructure Works - Abdul Ghani, A. Naser (Infrastructure Technology Research Unit, USM, 2007)
Load reduction effect of using lightweight material in new construction, expansion, rehabilitation or maintenance of infrastructure facilities provide advantages in term of reduction of total cost, construction time and maintenance work especially in soft ground areas.